Spy Chiefs - Moran, Christopher R. (Georgetown University Press, 2018)
This second volume of Spy Chiefs goes beyond the commonly studied spy chiefs of the United States and the United Kingdom to examine leaders from Renaissance Venice to the Soviet Union, Germany, India, Egypt, and Lebanon in the twentieth century.